The Future of Leadership Development Disruption and the Impact of Megatrends - Hieker, Carola; Pringle, John (Palgrave Macmillan, 2021)
Leadership development aims to disrupt leaders' behavioural and thought patterns. However, for many decades leadership development has not changed significantly: nobody seems to be disrupting the disrupters. It needs to evolve if leaders are to deal successfully with the disruptive challenges they face today - such as climate change, global health emergencies, digitization, an ageing workforce and the different expectations of millennials and Generation Z. This book reflects critically on the future of leadership development and what is missing in traditional approaches. It is based on interviews with leadership development suppliers, HR professionals and leaders, as well as the authors' industry experience. This book provides practical recommendations for how leadership development needs to change to support leaders as they navigate a volatile and uncertain world. Carola Hieker started her career as an internal HR professional with PwC before co-founding hilcoaching, a small consultancy-boutique. She has over 25 years of experience as a Senior Executive Coach and Change Management Consultant in a wide range of industries. Carola is an Honorary Associate Professor of UCL and an Associate Professor of Leadership and Organisational Behaviour at Richmond, The American International University in London, UK. John Pringle runs a Leadership Development Consultancy and has over 25 years of experience working with organisations from many sectors across the world, from banks to supermarkets. He spent 14 of these years in leadership roles within the Unilever group